Analisis Pengaruh Faktor Internal dan Eksternal terhadap Efisiensi Bank Umum Konvensional di Indonesia Periode 2012-2016 dengan Menggunakan Two Stage Data Envelopment Analysis - FATMAWATI, RIANA; SENO AJI, TONY (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract The study using a sample of 150 conventional banks in Indonesia and consisted of two stages, the first stage using Data Envelopment Analysis to analyze the level of efficiency of conventional banks in Indonesia in the year 2012-2016 with DEAP 2.1. The second stage used tobit methods to analyze suspected the factors to affect the level of coventional bank efficiency in Indonesia which consists of Return On Assets (ROA),Capital Adequacy Ratio (CAR) the size of banks, Non Performing Loan (NPL), Gross Domestic Product (GDP), and the number of bank branches by using Eviews 9. The result in the first stage using DEA analysis indicates that there are only five banks were 100% efficient during the study period include: Bank Central Asia Tbk, Bank Negara Indonesia Tbk, Bank Mandiri Tbk, Bank Danamon Tbk, and Bank of India Indonesia Tbk. While other banks have experienced inefficiency during the study period and some banks are only experiencing efficiency in a certain year only. In the second stage using tobit methods, it is known that ROA, the bank size, and NPL influence on the bank efficiency. CAR, GDP, and the number of bank branches have no effect on the efficiency of coventional banks in Indonesia in 2012-2016. So, to achieve maximum efficiency, the bank needs to pay attention to several internal factors such as profitability, bank size, and non performing loan. Keywords: bank efficiency, data envelopment analysis, tobit.